2020
DOI: 10.1183/13993003.00612-2020
|View full text |Cite
|
Sign up to set email alerts
|

Asthma medication use in obese and healthy weight asthma: systematic review/meta-analysis

Abstract: BackgroundObesity is a common co-morbidity in asthma and associated with poorer asthma control, more frequent/severe exacerbations, and reduced response to asthma pharmacotherapy.ObjectiveThis review aims to compare use of all classes of asthma medications in obese (BMI≥30 kg·m−2) versus healthy weight (BMI<25 kg·m−2) subjects with asthma.DesignDatabases including CINAHL, Cochrane, EMBASE, and MEDLINE were searched for English language studies up to July 2019 that recorded medication use or dose in obese an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…For example, patients with asthma and comorbid obesity experience more symptoms, more frequent and severe exacerbations, greater impairment of QoL, and have a reduced response to several asthma medications versus people with asthma and healthy weight [68]. Patients with obesity and asthma have been demonstrated to have higher asthma medication use than asthma patients with healthy weight, despite lower lung function [69]. Weight loss has also been demonstrated to be effective in improving asthma outcomes [70,71].…”
Section: Impact Of Comorbiditiesmentioning
confidence: 99%
“…For example, patients with asthma and comorbid obesity experience more symptoms, more frequent and severe exacerbations, greater impairment of QoL, and have a reduced response to several asthma medications versus people with asthma and healthy weight [68]. Patients with obesity and asthma have been demonstrated to have higher asthma medication use than asthma patients with healthy weight, despite lower lung function [69]. Weight loss has also been demonstrated to be effective in improving asthma outcomes [70,71].…”
Section: Impact Of Comorbiditiesmentioning
confidence: 99%
“…Although obesity is common in patients with severe eosinophilic and allergic asthma, obesity is known to increase disease severity, and obese patients are more likely to use more asthma medications than healthy-weight asthmatics. 13 However, there is increasing evidence that obesity-related asthma is driven by T H 2-independent inflammatory processes, 14 so may represent a more complex and drug-resistant asthma phenotype. Indeed, a preliminary study of six overweight and six obese patients receiving mepolizumab, dupilumab, or reslizumab revealed significantly worse ACQ scores (but not in lung function) in obese compared to non-obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is increasingly recognized as a disease modifier in asthma, which subsequently complicates asthma management. Compared with non-obese people with asthma, individuals with comorbid obesity and asthma appear to have more difficult to control disease ( 36 ) with worsened asthma symptoms (such as dyspnoea and wheezing) ( 40 ), fewer symptom-free days ( 41 , 42 ), lower exercise capacity ( 43 ), reduced lung function ( 44 ), and lung volumes ( 45 ), increased frequency and severity of asthma exacerbations ( 36 ), increased risk of asthma-related hospitalizations ( 46 ), and poorer asthma-related quality of life (QoL) ( 47 ). In fact, BMI has been found to be an independent predictor of poor QoL ( 48 ), with QoL more than five times worse in people with asthma who are obese compared to those who are non-obese ( 49 ).…”
Section: The Impact Of Extrapulmonary Comorbidities/traits In Asthmamentioning
confidence: 99%
“…Individuals with comorbid asthma and obesity have also been found to use more asthma medications compared to those without obesity ( 53 ). In a recent systematic review and meta-analysis by Thompson and colleagues, obesity was found to be associated with increased odds of any asthma medication use, which included inhaled bronchodilators [short-acting (SABA) and long-acting (LABA, anticholinergic)], inhaled controller medications [inhaled corticosteroids (ICS, as well as combined ICS and LABA)], and oral preventer medications [maintenance oral corticosteroid (OCS), Leukotriene receptor antagonists (LTRA)] ( 44 ). Daily ICS doses were also significantly higher in obese individuals with asthma compared with their healthy-weight (BMI <25 kg/m 2 ) counterparts ( 44 ).…”
Section: The Impact Of Extrapulmonary Comorbidities/traits In Asthmamentioning
confidence: 99%